ENHANCING STUDENT ENGAGEMENT AND READING IN NARRATIVE LITERACY WITH QUICK MAKER - Marpaung, Syafaruddin (SEAQIL Journal of Language Education, 2025)
This Classroom Action Research (CAR) study investigates the impact of the Quick Maker method (Quizizz Cara Kertas Memakai Atribut Kemerdekaan dan Stiker) on student engagement and narrative text literacy. Conducted with 34 students from one class at a senior high school in Tanjungbalai, data were collected through questionnaires, interviews, and observations. The research followed Stringer's (2007) "spiral of action research" framework, incorporating two cycles of intervention. In the first cycle, the average student engagement score increased from 3.2 to 3.7 on a 5-point scale, with the percentage of students who felt highly engaged rising from 25% to 40%. After adjustments and improvements in the second cycle, the engagement score further increased to 4.1, with 60% of students reporting high engagement. Similarly, narrative text test scores improved from an average of 70 before the intervention, to 77 after the first cycle, and 85 following the second cycle. The method involved incorporating independence-themed attributes, such as hats to instill a sense of nationalism, while motivational stickers were awarded to the top 15 students in both cycles. This student-centered approach effectively increased student participation, fostered peer learning, and enhanced narrative text literacy. The results demonstrate that integrating interactive technology with motivational tools can significantly improve student engagement and performance in reading literacy.